High resolution : critical theory and the problem of literacy - Sussman, Henry (Oxford University Press, 1989)
This book combines literary theory and close textual readings of works by Hawthorne, Melville, Wallace Stevens, William Carlos Williams, Ezra Pound and Italo Calvino to explore the socio-political correlatives to literary studies.